Left bundle branch pacing and cardiac remodeling in HF patients with type 2 diabetes mellitus: epigenetic pathways and clinical outcomes - Sardu, Celestino; Vittoria Marfella, Ludovica; Giordano, Valerio; Lepre, Caterina Claudia; D’Amico, Giovanbattista; Volpicelli, Mario; Contaldi, Carla; Galiero, Raffaele; Caturano, Alfredo; Casolaro, Flavia; Sasso, Ferdinando Carlo; Uran, Carlo; et al. (Frontiers in Pharmacology, 2024)
Background Left bundle branch (LBB) pacing could achieve cardiac resynchronization therapy (CRT) in patients who cannot be resynchronized via the placement of the left ventricle (LV) lead into the coronary sinus. LBB pacing could improve cardiovascular outcomes in heart failure (HF) patients with LBB block who are affected by type 2 diabetes mellitus (T2DM). Study hypothesis LBB pacing could increase the number of CRT responders and lead to the best clinical outcomes in HF patients with T2DM, inducing cardiac remodeling and improving left ventricle ejection fraction (LVEF) via microRNA (miR) modulation. Methods In a multicenter observational study, we enrolled 334 HF patients with LBB block and an indication to receive LBB pacing for CRT. In these patients, we evaluated the CRT responder rate, clinical outcomes, and miR expression at 1 year of follow-up. Results At 1 year of follow-up, we had 223 responders (66.8%), 132 hospitalizations for HF (39.5%), 24 cardiac deaths (7.2%), and 37 all-cause deaths (11.1%), with a higher rate of HF hospitalizations (77 (69.4%) vs 55 (24.7%), p < 0.05), and cardiac deaths (13 (11.7% vs 11 (4.9%), p < 0.05) in non-responders vs responders. At the end of follow-up, we found the lowest expression of miR-26, miR-29, miR-30, miR-92, and miR-145 in LBB-pacing non-responders vs responders (p < 0.05), and a direct correlation between miR-30 (0.340, [0.833–1.915]; p 0.001), the 6-minute-walking test (6MWT; 0.168, [0.008–0.060]; p 0.011), angiotensin-receptor-neprilysin inhibitors (ARNI; 0.157, [0.183–4.877]; p 0.035), sodium-glucose-transporter-2 inhibitors (0.245, [2.242–7.283]; p 0.001), and LVEF improvements. C reactive protein (CRP) inversely correlated with LVEF improvement (−0.220, [-(0.066–0.263)]; p 0.001). ARNI (1.373, CI 95% [1.007–1.872], p 0.045), miR-30 (2.713, CI 95% [1.543–4.769], p 0.001), and 6MWT (1.288, CI 95% [1.084–1.998], p 0.001) were predictors of LBB pacing responders at 1 year of follow-up. Conclusion LBB-pacing responders evidenced miR modulation, which was linked to significant improvement of the cardiac pump. Specifically, miR-30 was linked to cardiac pump improvement and predicted responders at 1 year of follow-up in patients with T2DM.